Kastil Shuri di Prefektur Okinawa: Pelestarian Identitas Budaya Ryukyu dan Destinasi Wisata - Qintara Rinda; Nisia Nur Dwi Agusta (Janaru Saja Jurnal Program Studi Sastra Jepang, 2026)
Abstract Shuri Castle is one of the historical sites that represents the cultural identity of the Okinawan people. In the past, this castle functioned as the political and cultural center of the Ryukyu Kingdom. In the present day, Shuri Castle is not only a historical heritage site but also serves as a symbol of the preservation of Ryukyuan cultural identity as well as an important cultural tourism destination in Okinawa. This study aims to analyze the role of Shuri Castle in maintaining Ryukyuan cultural identity and to understand its transformation as a tourism destination in Okinawa. The research method used is a qualitative method with a descriptive approach through literature study and historical analysis, as well as an examination of the symbolic values and contemporary functions of the castle using Stuart Hall’s theory of cultural identity. The results of this study indicate that Shuri Castle has a strategic role as a representation of Ryukyuan cultural identity through its architecture, political history, and the symbolic meanings embedded within the Shuri Castle complex. In addition, the management of Shuri Castle as a historical park and tourist destination supports efforts to preserve cultural heritage and enhances public understanding of Okinawan history and culture. Keywords: Shuri Castle, Okinawa, Ryukyuan cultural identity, tourism.   Abstrak Kastil Shuri merupakan salah satu tempat bersejarah yang merepresentasikan identitas budaya masyarakat Okinawa. Dahulu kastil ini berfungsi sebagai pusat politik pemerintahan dan kebudayaan dari Kerajaan Ryukyu. Di masa sekarang, Kastil Shuri tidak hanya sebagai tempat peninggalan sejarah, tetapi juga sebagai simbol pelestarian identitas budaya Ryukyu serta kawasan pariwisata budaya yang penting di Okinawa. Penelitian ini bertujuan untuk menganalisis peran Kastil Shuri dalam mempertahankan identitas budaya Ryukyu dan memahami perubahannya sebagai destinasi pariwisata di Okinawa. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif melalui studi literatur dan analisis historis, serta kajian terhadap nilai simbolis dan fungsi kontemporer kastil menggunakan teori identitas budaya dari Stuart Hall. Hasil penelitian menunjukkan bahwa Kastil Shuri memiliki peran strategis sebagai representasi identitas budaya Ryukyu melalui arsitektur, sejarah politik, dan makna simbolis yang melekat pada kawasan Kastil Shuri tersebut. Selain itu, pengelolaan Kastil Shuri sebagai taman sejarah dan destinasi wisata turut mendukung upaya pelestarian warisan budaya serta meningkatkan pemahaman masyarakat terhadap sejarah dan kebudayaan Okinawa. Kata kunci: Kastil Shuri, Okinawa, identitas budaya Ryukyu, pariwisata.